Spectrophotometric determination of Aspirin and Pyridoxine Hydrochloride using 9- Chloroacridin reagent in aqueous solution - Intisar Shehab; Theiaa Al-Sabha (College of Education for Pure Sciences, 2020)
This research paper tackles a developed method for Aspirin and Pyridoxine drugs determination in their pure forms and pharmaceutical formulations. It is based on the formation of nucleophilic substitution reaction between given drugs and 9-Chloroacridine forming a reddish orange colours. The products show maximum absorption at 532 nm and 534 nm for Aspirin and Pyridoxine respectively. The method was adhering to the Beer's law over concentration range 0.2-18 and 0.4-24 µg/ml with molar absorptivity values 1.1×104 and 7×103 l. mol-1. cm-1 and average recovery 99.87% and 100.00 % for the given drugs respectively. No observed interferences appeared from the excipients commonly existed in pharmaceuticals. Successfully, application for both Aspirin and Pyridoxine was conducted in their pharmaceutical formulations. The continuous variations and the slope ratio of the products between Aspirin and pyridoxine hydrochloride were followed with 9-chloroacridine. The ratio of 1: 1 was obtained between the above two drugs and the reagent The stability constant of the products was 6.38 x 104 and 9.25 × 104 l / mol for both Aspirin and Pyridoxine Hydrochloride products respectively indicating the good stability of these products.